Radical Reversal of Vasoactive Intestinal Peptide Receptors During Early Lymphopoiesis - Vomhof-DeKrey, Emilie E. (2011)
Successful thymocyte maturation is essential for normal, peripheral T cell function. Vasoactive intestinal peptide (VIP) is a neuropeptide which is highly expressed in the thymus that has been shown to modulate thymocyte development. VIP predominantly binds two G protein coupled receptors, termed vasoactive intestinal peptide receptor 1 (VPAC1) and VPAC2, but their expression profiles in CD4(−)/CD8(−) (double negative, DN) thymocyte subsets, termed DN1–4, have yet to be identified. We hypothesized that a high VPAC1:VPAC2 ratio in the earliest thymocyte progenitors (ETP cells) would be reversed during early lymphopoiesis as observed in activated, peripheral Th(2) cells, as the thymus is rich in Th(2) cytokines. In support of this hypothesis, high VPAC1 mRNA levels decreased 1000-fold, accompanied with a simultaneous increase in VPAC2 mRNA expression during early thymocyte progenitor (ETP/DN1) → DN3 differentiation. Moreover, arrested DN3 cells derived from an Ikaros null mouse (JE-131 cells) failed to completely reverse the VIP receptor ratio compared to wild type DN3 thymocytes. Surprisingly, VPAC2(−/−) mice did not show significant changes in relative thymocyte subset numbers. These data support the notion that both VPAC1 and VPAC2 receptors are dynamically regulated by Ikaros, a master transcriptional regulator for thymocyte differentiation, during early thymic development. Moreover, high VPAC1 mRNA is a novel marker for the ETP population making it enticing to speculate that the chemotactic VIP/VPAC1 signaling axis may play a role in thymocyte movement. Also, despite the results that VPAC2 deficiency did not affect thymic subset numbers, future studies are necessary to determine whether downstream T cell phenotypic changes manifest themselves, such as a propensity for a Th(1) vs Th(2) polarization.